An application of Stafford and Warr's reconceptualization of deterrence to drinking and driving - Piquero, Alex R. (Journal of research in crime and delinquency, 1998)
In a recent restatement of the deterrence doctrine, Stafford and Warr 1993 argued that deterrence is felt through a mixture of personal and vicarious experiences with punishment and the avoidance of punishment. An implication of the premise that persons may be affected by both what they directly experience and what they only indirectly experience through others is that they may be influenced by both general and specific deterrence mechanisms. In an empirical test of this reconceptualization, the authors found that persons' expressed intentions to drink and drive are affected by 1 personal and vicarious experiences and 2 punishment and punishment avoidance. Strong deterrent effects were found for the perceived certainty of punishment that is directed at one's self. The authors also found that moral beliefs that prohibit drunk driving are an effective source of inhibition. In addition, the social control of drunk driving seems to operate equally well for men and women